2021
DOI: 10.1007/s10508-021-01951-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Coronavirus Disease (COVID-19) on the Health and Social Needs of Sex Workers in Singapore

Abstract: We evaluated the impact of the coronavirus disease (COVID-19) on the sex work industry and assessed how it has impacted the health and social conditions of sex workers in Singapore. We conducted a sequential exploratory mixed methods study amidst the COVID-19 pandemic from April to October 2020, including in-depth interviews with 24 stakeholders from the sex work industry and surveyor-administered structured surveys with 171 sex workers. COVID-19 had a substantial impact on sex workers' income. The illegality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…To our knowledge, our study is one of the first large-scale surveys to report on the challenges encountered by FSWs during the pandemic. It quantitatively confirms what has been subjectively expressed by FSWs in previous qualitative studies [4,22,23]. It further identifies specific layers within the FSW community that need prioritized interventions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To our knowledge, our study is one of the first large-scale surveys to report on the challenges encountered by FSWs during the pandemic. It quantitatively confirms what has been subjectively expressed by FSWs in previous qualitative studies [4,22,23]. It further identifies specific layers within the FSW community that need prioritized interventions.…”
Section: Discussionsupporting
confidence: 83%
“…Our data show that the shift to online sex work does not guarantee an income adequate to support FSWs' needs; i.e., taking up online sex work was not a determinant of the likelihood of suffering a major income reduction (Tables 4 and S2). This result is also noted in other qualitative studies [4,23]. Meanwhile, only around 40% of FSWs were found to adequately adhere to COVID-19 prevention measures during sex work, highlighting their risk of exposure to COVID-19 infection for a significant number of FSWs during the pandemic.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…While the present study was underpowered to detect differences in financial concern across demographic variables (i.e., race, ethnicity, sexual orientation), authors continue to support the assertion that subgroups of sex workers are more likely to experience additional adversity. For example, a study of sex workers in Singapore during COVID-19 found that noncitizenship status and being a transgender woman were associated with greater loss of income and increased housing and food insecurity (Tan et al, 2021). For groups that face additional layers of exclusion from resources and more ubiquitous oppression (e.g., xenophobia, racism), public health, and emergency legislation as well as economic relief will need to bolster sex worker organization efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Academic media analyses [33,13] were a fast and efficient way to analyse the situation for sex workers in the pandemic, documenting daily life impacts such as movement restrictions, food insecurity, homelessness; violence and exclusion from government schemes; and the response from sex worker rights organisations. Some researchers managed swift qualitative research with sex workers, with findings echoing those of NGOs and the media analyses [16,94,122,132,64,100]. In some places, the closure or interruption of healthcare services, meaning sex workers struggled to access for example HIV prevention or treatment, was of great concern [52,86,134], as was the mental health of sex workers dealing with these issues on top of increased stigma and violence [74].…”
Section: Sex Work In the Pandemicmentioning
confidence: 99%